1990
DOI: 10.1159/000226812
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incomplete Bile Duct Obstruction on the Occurrence of Cholangiocarcinoma Induced by Diisopropanolnitrosamine in Hamsters

Abstract: This study was performed to clarify the influence of incomplete bile duct obstruction (IBDO) on the occurrence of cholangiocarcinoma, using Syrian golden hamsters. These hamsters underwent simple laparotomy (SL) or IBDO at the choledochus and received diisopropanolnitrosamine (DIPN) once weekly for 20 weeks (SL-DIPN or IBDO-DIPN groups). Histological examination in the liver showed increased bile ductules, goblet cell metaplasia of the bile duct epithelium and cholangiocarcinoma in the two groups. The occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Yamamoto [19] reported that bile ductule proliferation w'as an important factor in the occurrence of cholangiocarcinoma in rats treated with diethylnitrosamine, and Kinami et al [20] performed a histological ex amination in cases of hepatolithiasis associated with cholangiocarcinoma and emphasized the relationship be tween hyperplasia in the bile duct epithelium and car cinogenesis. In our examination performed previously in hamsters [ 15], histological changes in the bile duct and its epithelium were observed, and in this study the histologi cal examination also demonstrated proliferation of bile ductules and papillary hyperplasia in the bile duct, reveal ing their high occurrence rates in the 2 groups treated with bile acids. On the other hand, Makino etal.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Yamamoto [19] reported that bile ductule proliferation w'as an important factor in the occurrence of cholangiocarcinoma in rats treated with diethylnitrosamine, and Kinami et al [20] performed a histological ex amination in cases of hepatolithiasis associated with cholangiocarcinoma and emphasized the relationship be tween hyperplasia in the bile duct epithelium and car cinogenesis. In our examination performed previously in hamsters [ 15], histological changes in the bile duct and its epithelium were observed, and in this study the histologi cal examination also demonstrated proliferation of bile ductules and papillary hyperplasia in the bile duct, reveal ing their high occurrence rates in the 2 groups treated with bile acids. On the other hand, Makino etal.…”
Section: Discussionsupporting
confidence: 79%
“…As seen in our previous report [15], in which the influ ence of incomplete bile duct obstruction on the occurrence of cholangiocarcinoma in hamsters was studied by using DIPN discovered by Althoffet al [16] and Pouret al [17,18], DIPN is useful in the experiments on cholangiocar cinoma because its occurrence is certain. The occurrence rates and tumor numbers of cholangiocarcinoma at 15 and 20 w'eeks in the TCA and DCA groups were high and fre quent compared with those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, hydrophilic acids such as ursodeoxycholic acid have protective effects such as prevention of gallstones through desaturation of bile and reduction of cellular changes seen in hepatic and biliary diseases 2-6. In animal models, cholic and deoxycholic acid have been implicated in the development of bile duct cancer 7,8. Increased levels of deoxycholic and lithocholic acid concentrations have also been reported in patients with choledochal cyst and anomalous union of the pancreaticobiliary duct 9.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have reported that through the continuous administration of DIPN dissolved in olive oil, neoplasms occur in the pancreas, liver, lung and other locations in hamsters [15,22,23]. In a previous study, neoplasms were induced not only in the liver but also in the pancreas or lung 20 weeks after beginning DIPN administration [17]. Pour et al [24] and Kajikawa et al [25] observed hemangioendothelioma, angiosarcoma or hepatoma, in addition to cholangioma and cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies on the relationship between bile acids and carcinogenesis in the biliary ductal system [13][14][15][16][17]. The bile duct epithelium is continuously exposed to bile, and changes in the composition of bile acids are caused by bile stasis resulting from stenosis, obstruction or infection of the bile duct.…”
Section: Introductionmentioning
confidence: 99%